2019
DOI: 10.1002/cam4.2524
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of Kinesin‐4 family genes mRNA expression in early‐stage pancreatic ductal adenocarcinoma patients after pancreaticoduodenectomy

Abstract: Background The aim of this study was to investigate the potential prognostic value of Kinesin‐4 family genes mRNA expression in early‐stage pancreatic ductal adenocarcinoma (PDAC) patients after pancreaticoduodenectomy. Methods Kaplan‐Meier survival analysis method with log‐rank test and Cox proportional hazards regression analysis were performed to figure out the association between Kinesin‐4 family genes expression and PDAC patients overall survival time. Joint‐effect survival analysis and stratified surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Lipids and lipid-like molecules dominated the correlations, indicating their conserved roles in CRC progression and treatment. Meanwhile, several important proteins including KIF21A, TAGLN2, PFN1, and SFTPB were positively correlated with each other ( 30 , 31 ). For example, the expression level of KIF21A was significantly related to the clinical prognosis outcome of pancreatic ductal adenocarcinoma (PDAC) patients; patients with increased levels of KIF21A had shorter overall survival (OS) time.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids and lipid-like molecules dominated the correlations, indicating their conserved roles in CRC progression and treatment. Meanwhile, several important proteins including KIF21A, TAGLN2, PFN1, and SFTPB were positively correlated with each other ( 30 , 31 ). For example, the expression level of KIF21A was significantly related to the clinical prognosis outcome of pancreatic ductal adenocarcinoma (PDAC) patients; patients with increased levels of KIF21A had shorter overall survival (OS) time.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies showed that ASPM expression was associated with the survival of cancer patients, and its upregulation resulted in a poor prognosis in breast cancer and pancreatic ductal adenocarcinoma (62,67). KIF4A and KIF20A are two members of the kinesin family that are mainly responsible for movement along the microtubules in the cell, which has been demonstrated to be associated with many diseases including cancers (68)(69)(70)(71). The other three genes including MELK, TOP2A and TYMS are enzyme-encoding genes, which separately play roles in BPs related to cell cycle regulation, chromosome status, and DNA replication and repair.…”
Section: Discussionmentioning
confidence: 99%